PENGARUH MODEL PEMBELAJARAN TWO STAY TWO STRAY TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Heppy Ester Sitanggang; Darinda Sofia Tanjung; Patri Janson Silaban; Bogor Lumbanraja; Risiki Bastanta B. Manalu (Universitas Negeri Medan, 2026)
This study aims to determine whether there is an effect of the Two Stay Two Stray learning model on students' learning outcomes in the fourth-grade IPAS subject,